Terminal-Restriction Fragment Length Polymorphism (T-RFLP) Analysis for Changes in the Gut Microbiota Profiles of Indomethacin- and Rebamipide-Treated Mice - Imaeda, Hirotsugu; Fujimoto, Takehide; Takahashi, Kenichiro; Kasumi, Eiji; Fujiyama, Yoshihide; Andoh, Akira (Digestion, 2012)
Background/Aims: We investigated the effects of indomethacin and rebamipide on the gut microbiota profiles using terminal restriction fragment polymorphism (T-RFLP) analysis. Materials and Methods: Female C57BL/6J mice were given indomethacin (10 mg/kg, s.c.) once a day and 2.5 mg rebamipide orally 3 times a day. After 7 days, they were sacrificed, and luminal contents were obtained from the ileum and cecum. The gut microbiota communities were analyzed by T-RFLP analysis with BslI digestion. Results: T-RFLP analyses showed that rebamipide and indomethacin had no significant effects on the gut microbiota profiles in the ileum and cecum. In contrast, the combination of rebamipide + indomethacin induced a significant change in the gut microbiota. The changes in the microbiota composition induced by the combination of rebamipide + indomethacin were characterized by the increase in the orders Bifidobacteriales and Lactobacillales, the genera Bacteroides and Prevotella and the family Clostridiaceae. The diversity of the gut microbiota community generated by the combination of rebamipide + indomethacin was significantly higher than those induced by either rebamipide or indomethacin alone. Conclusion: The combination of rebamipide + indomethacin induces remarkable changes in the gut microbiota composition and diversity. The clinical activity of rebamipide on nonsteroidal anti-inflammatory drug-induced intestinal injury may be exerted through a modulation of the gut microbiota.